Sacchrification of Corn Cobs by Cellulases Producer by Trichoderma SPP. and Cellulomonas and Production of SCP - Jabbar, F. Al-maadhidi; Marwa, A. Hadab (Journal of Madenat Alelem University College, 2013)
Thousand tons of corn cobs were accumulated yearly in Iraq, which are rich in cellulose and poor in protein. The sacchrification of corn cobs can be used for cultivation of yeast and production of single cell protein (SCP). Two microorganisms producing cellulases were used for conducting experiments, Trichoderma spp. and Cellulomonas. The most productive strain of Trichoderma spp. was chosen after assaying all isolates. Results revealed that fungal isolates was more efficient in producing sugar from corn cobs than bacteria. Maximum concentration of sugar was produced by fungal culture after nine days of incubation time in surface and submerged culture, while it was not efficient in fermenter. Cellulases were induced to release from bacterial cells and increased with incubation period. Fermenter experiment showed the ability of yeast to utilize sugar produced from corn cob leading to increase protein content to 14.3٪ and fibers was reduced from 41.7٪ to 10.9٪ which became more suitable for feeding ruminants and fish.